Effect of concurrent lower genital tract infections on cervical cancer screening. - Schwebke, J R (1997)
BACKGROUND AND OBJECTIVES: Although women attending STD clinics are at high risk for cervical cancer, most STD programmes do not include Papanicolaou (Pap) smears in their routine screening procedures. Concerns regarding reliability of this test in a population with a high rate of active infection are often raised. The objective of this study was to analyse the associations between STD diagnosis/clinical syndromes and unsatisfactory and abnormal Pap smears. METHODS: Retrospective analysis of Pap results and medical records from women attending an inner city STD programme. RESULTS: Of the 1202 patients analysed, 3.2% had squamous intraepithelial lesions (SIL) and 3.5% had smears which were unsatisfactory because of the thickness of the specimen. There were no associations between STD diagnoses and SIL; however, the presence of cervical inflammation was significantly associated with SIL. Pap smears which were unsatisfactory because they were too thick were also associated with the clinical finding of cervical inflammation. CONCLUSIONS: The presence of active infection did not preclude the detection of SIL on Pap smears. The percentage of unsatisfactory smears resulting from inflammation was low.